Tingkat Pengetahuan Dan Sikap Mahasiswa Farmasi Universitas Bhamada Slawi Mengenai Bahaya Bahan kimia Pada Produk Kecantikan Tanpa Izin Edar BPOM - Dina Syabrina lutfa; Fika Rizqiyana; Prihastini Setyo Wulandari; Endang Istriningsih (Program Studi Farmasi, Universitas Ma Chung, 2025)
The increasing use of beauty products among university students, especially females, raises concerns about the potential risks of harmful chemical ingredients, particularly in products lacking distribution authorization from Indonesia’s National Agency for Drug and Food Control (BPOM). As future healthcare professionals, pharmacy students are expected to possess strong knowledge and awareness about the safety of cosmetic products. This study aims to assess the level of knowledge and attitudes of pharmacy students at Universitas Bhamada Slawi regarding the dangers of chemical substances in unlicensed beauty products, and to analyze the relationship between the two variables. This descriptive quantitative research involved 246 pharmacy students selected using purposive sampling. Data were collected through a validated online questionnaire and analyzed using univariate analysis and the chi-square test. The findings revealed that 72.4% of students had an excellent level of knowledge, 26.4% had good knowledge, 0.8% fair, and 0.4% poor. Most respondents also showed a cautious and responsible attitude in selecting beauty products. Statistical analysis indicated a significant correlation between knowledge and attitude (p < 0.001), suggesting that students with higher knowledge levels are more selective in choosing safe cosmetic products. This study concludes that higher levels of knowledge significantly influence students’ awareness and behavior toward the use of safe, BPOM-approved beauty products. The results can serve as a foundation for further education and public health promotion related to cosmetic safety and regulation.